Management of persistent patellofemoral pain conditions using a tricompartmental offloading knee brace: a case series. - Okrainetz, Jonathan; Boon-van Mossel, Nathan (Journal of the Canadian Chiropractic Association, 2024)
Objective: To describe the utility of a tricompartmental offloading knee brace as an adjunct intervention for managing persistent PFP conditions. Clinical features: Three cases of active adult females with persistent PFP following non-response to conventional and guideline aligned management strategies are presented. Intervention and outcomes: Patients were managed using a tricompartmental offloading knee brace alongside individualized exercise programs for up to 12 weeks. Subjective and objective measures of pain and function were measured at three distinct time points. Each patient reported decreased pain, increased activity tolerance, and demonstrated improvements in both strength and functional performance over the course of the intervention period. Summary: The use of tricompartmental offloading knee bracing alongside exercise therapy may be effective for the management of persistent PFP and should be considered for active adult females if unresponsive to both conventional and guideline aligned treatments.